Cerebral venous sinus thrombosis following Russell's viper (Daboia russelii) envenomation: A case report and review of the literature. (30th October 2022) - Ghosh, Ritwik; León-Ruiz, Moisés; Roy, Dipayan; Naga, Dinobandhu; Sardar, Sona Singh; Benito-León, Julián
Abstract: Snakebite is a life-threatening and often-neglected public health hazard with high chronic disability and mortality, mainly faced by rural communities in the tropics/subtropics. Stroke and neuromuscular paralysis are the most severe neurological complications. However, cerebral venous sinus thrombosis has rarely been reported among cerebrovascular complications. We report a previously healthy middle-aged Indian woman who developed cerebral venous sinus thrombosis preceded by features of disseminated bleeding diathesis following Russell's viper bite. The cerebral venous sinus thrombosis was diagnosed by magnetic resonance imaging. The patient responded well to treatment with antivenom and subcutaneous enoxaparin and had no demonstrable neurological deficits at three months of follow-up. Graphical abstract: Image 1 Highlights: Cerebral venous sinus thrombosis is extremely rare following snakebite envenoming. Snake venom contains substances causing thrombotic-embolic and hemorrhagic strokes. We report a patient who developed cerebral venous sinus thrombosis following Russell's viper bite.